Anti-radical flavonol glycosides from the aerial parts of Cleome chelidonii L.f. (October 2017) - Nguyen, Phuc-Dam; Sayagh, Charlotte; Borie, Nicolas; Lavaud, Catherine
Abstract: Eleven previously undescribed flavonoid glycosides, named cleomesides C-M, along with five known compounds, were isolated from the aerial parts of Cleome chelidonii L.f. (Cleomaceae). All flavonol glycosides were esterified derivatives of 3, 7- O -diglycosides of quercetin or kaempferol. Their structures were elucidated by analysis of the 1D and 2D NMR spectra, HR-ESI-MS data, UV spectra, optical rotation and by comparison with literature data. The DPPH radical scavenging properties of the flavonoid glycosides were studied in order to appreciate the effect of the glycoside parts and of the ester groups on this activity compared with the quercetin and kaempferol aglycones. An acetate at position 3 of rhamnose linked to C-7 of flavonol, gave compounds with the strongest antiradical activity. An aromatic ester group at position 6 of terminal glucose of diglycoside chain linked to C-3 of flavonol did not seem to influence the antiradical activity. Graphical abstract: Eleven flavonol glycosides named cleomesides C-M, along five known compounds, were isolated from the aerial parts of Cleome chelidonii L.f. (Cleomaceae). These were esterified derivatives of 3, 7- O -diglycosides of quercetin or kaempferol. Their antiradical activity was assessed by the DPPH-test in order to evaluate the effect of the miscellaneous substituents. Highlights: Eleven previously undescribed flavonoids were isolated from Cleome chelidonii. Hydroxycinnamoyl esterified flavonoids were characterized. Anti-radical activities of the compounds were evaluated. The presence of a 3- O -acetyl-rhamnose showed the best anti-radical activity.